“Left Atrial Appendage Closure Versus Medical Therapy in Atrial Fibrillation: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials” - Ali Alsajad Hussein Al‐Janabi; Ali Saad Al‐Shammari; Ahmed W. Hageen; Abdullah Zeyad Hameed Al‐Tuaama; Abdullah Muataz Taha Al‐Ibraheem; Muhammad Shahzaib; Diya Rathi; Khadeeja Ali Hamzah; Mohammedsadeq A. shweliya; Yousif Hameed Kurmasha; Mohamed Wagdy; Marwan M. Refaat (Journal of Cardiovascular Electrophysiology, 2026)
ABSTRACT We aim to compare the impact of left atrial appendage closure vs. medical therapy on clinical outcomes in patients with atrial fibrillation, focusing on key clinical outcomes relevant to thromboembolic prevention. We conducted a PRISMA‐guided systematic review and meta‐analysis of studies comparing LAAC with medical therapy in AF adults. PubMed, Embase, Scopus, ClinicalTrial. gov, and Cochrane Library were searched from inception to March 2026. Outcomes included all‐cause mortality, any stroke, ischemic stroke, hemorrhagic stroke, major bleeding, systemic embolism and cardiac death. Risk ratios (RRs) with 95% confidence intervals (CIs) were pooled using random‐effects models. Reconstructed individual patient‐level survival data from published Kaplan–Meier curves were used for time‐to‐event analyses. Trial sequential analysis (TSA) assessed the conclusiveness of cumulative evidence. Six randomized controlled trials involving 7004 patients were included. LAAC demonstrated comparable outcomes to medical therapy for all‐cause mortality, any stroke, major bleeding, systemic embolism, and cardiac death. There was a non‐significant trend toward increased ischemic stroke and reduced hemorrhagic stroke with LAAC. Reconstructed time‐to‐event analyses showed similar cumulative incidence of stroke and bleeding outcomes over follow‐up. TSA demonstrated that the required information size was not reached for any major endpoint, indicating that current evidence remains underpowered and additional randomized trials are needed. LAAC provides similar overall efficacy and safety compared with medical therapy for stroke prevention in AF but should currently remain reserved for selected patients rather than replacing oral anticoagulation broadly. Further adequately powered trials with longer follow‐up are required.